2016
DOI: 10.1021/acs.energyfuels.5b02586
|View full text |Cite
|
Sign up to set email alerts
|

Ash Fusion Properties from Molecular Dynamics Simulation: Role of the Ratio of Silicon and Aluminum

Abstract: Molecular dynamics simulations are adopted to investigate the effect of the ratio of silicon and aluminum (S/A) contents on ash fusion properties and to predict the theoretical melting points and viscosities. The melting points are identified by the variation of the volume and mean square displacement, while viscosities are calculated by the Green–Kubo formula. The melting point is determined to be higher for coal ash systems with higher S/A ratios. The analyses of the radial distribution function and oxygen c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…However, it is reported that Ca 2 Al 2 SiO 7 is likely to reacts with Ca 2 SiO 3 , NaAlSi 3 O 8 , and some Fe‐bearing compounds to give amorphous eutectic minerals. Those eutectic minerals will cover other minerals and results in serious ash deposition 17,28,29 . As a result, the samples show a severe molten phenomenon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is reported that Ca 2 Al 2 SiO 7 is likely to reacts with Ca 2 SiO 3 , NaAlSi 3 O 8 , and some Fe‐bearing compounds to give amorphous eutectic minerals. Those eutectic minerals will cover other minerals and results in serious ash deposition 17,28,29 . As a result, the samples show a severe molten phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…Qi et al 15 and Tao et al 16 find Ca–Na‐bearing minerals will go through decomposition, evaporation, and interaction to convert to molten phase during the combustion. Dai et al 17 find that Ca atoms tend to transform to eutectic minerals with Al–O bond, decreasing the AFTs, with FactSage, one chemical thermodynamic equilibrium software 18 . Many researches also use FactSage to study the elements release, minerals transformation, and deposition behavior 19–21 …”
Section: Introductionmentioning
confidence: 99%
“…Figure 8 shows the radial distribution function and coordination number at a CaF2 content of 9%. The abscissa corresponds to the first peak of the radial distribution function [30] in Figure 8a Figure 7 shows the bonding state of the F ions when the content CaF 2 content was 9%. It can be observed that at 1673 K, the F ions formed a bond between the Al ligand structure and the Si ligand structure.…”
Section: Flurine Slag Viscosity Performance Test and Results Analysismentioning
confidence: 99%
“…Combined with the bond length of each ion pair in the simulated slag system and the full width at the half maximum of the first peak, it can be observed that the bonding ability of the Si-O bond was the strongest and Figure 8 shows the radial distribution function and coordination number at a CaF 2 content of 9%. The abscissa corresponds to the first peak of the radial distribution function [30] in Figure 8a, which is the bond length between the particles in the mold flux, and the bond lengths of Si-O, Ca-O, and Al-O were 1.625, 2.225, and 1.725 Å, respectively. Matsui [31] conducted an X-ray diffraction experiment to determine the silicate melt structure.…”
Section: Flurine Slag Viscosity Performance Test and Results Analysismentioning
confidence: 99%
“…Current studies on AMP of coal can be roughly divided into two categories: (i) the mechanism models that are based on the mechanism of chemical reactions; (ii) the empirical models that are based on data statistics. A large number of researchers have developed mechanism models in their studies on AMP of coal, for example, Chakravarty et al [14], Dai et al [15], Weber et al [16], Kim et al [17]. However, the mechanism models are very theoretical, with many assumptions, so the reaction process expressed by these formulas may deviate from the actual reaction process due to these assumptions.…”
Section: Introductionmentioning
confidence: 99%